A new method for waterjet peening process improvement using a combination of waterjet surface hardening and polishing - Mohd Azmir, Mohd Azhari (2014)
The present study investigates a combined effect of waterjet peening and smoothing on the surface of austenitic stainless steel 304. An analysis of surface and sub-surface integrity was conducted. The waterjet treatment on the surface was done in steps with multiple passes. The surfaces treated with multiple steps of decreasing energy produced a smoother surface with lower peak heights and a slightly higher increase in the hardness than the surface treated with only a single step. The results of XRD measurements showed that a higher amount of compressive residual stresses is induced in the treated specimens. This strengthening layer is limited within the first 100 μm below the surface, which had been confirmed by micro hardness measurements. The combined action of surface hardening and smoothing using multiple steps in waterjet treatment is useful in increasing the hardness and reducing the roughness of the surface. However, the treated specimens showed that the fatigue limit is lower than that of the untreated specimens. The slight roughness of the surface and the resulting notch effect seems to be stronger than the positive effect of the strengthend layer.